ANALISIS PERBANDINGAN STRUKTURAL CERPEN “SELAMAT JALAN NEK” KARYA DANARTO DENGAN CERPEN “POHON” KARYA MONAJ DAS - Anwar Efendi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2010)
This study aims to describe similarities in literary works written by authors with different cultural backgrounds, namely Indonesian and Indian. The data sources were Selamat Jalan Nek!, a short story by Danarto (an Indonesian author), and Pohon by Monaj Das (an Indian author). The comparative analysis was done by thoroughly reading and comprehending them, identifying similarity points in the structural aspect, and comparing and interpreting such points. The findings show that sequences of events constituting the plots of the two short stories have similarities from the beginning to the end. The ways the authors present the characters are similar, especially in physiological and sociological aspects of the characters. The themes are also similar, namely conflicts between modernity represented by the young generation and traditionality represented by the old generation. The datashow that the similarities are attributable to analogy.